New Social Movement on Jokowi’s Impeachment Action in Indonesia - Nurfebriansyah, Ahmad Rifki (JPP (Jurnal Politik Profetik), 2024)
The elections in Indonesia in 2024 have ended and confirmed the candidate pair Prabowo Subianto and Gibran Rakabuming Raka as the elected president and vice president to lead Indonesia. One of the controversies in 2024 election that occurred was President Jokowi's abuse of power with the aim of winning certain candidate pairs in the elections. Therefore, some people created a group called Petisi 100 to carry out a social movement, namely the impeachment of Jokowi. This movement can be categorized as New Social Movements (NSMs). This research aims to explore the Jokowi impeachment movement as NSMs which includes what is behind it, who is involved in the pros and cons, how the development process is, what activities mark it, the opportunity structure, mobilization and framing, and what impact it has on political dynamics in Indonesia. The research results show that the movement to impeach Jokowi was carried out due to dissatisfaction with Jokowi who was considered too involved in the 2024 elections. This movement developed through five stages, namely identity formation, escalation, mobilization, polarization, and actor formation. This movement could have an impact on challenges to political parties in channeling their aspirations and the results of the 2024 Election.